Progressive Relationship Between Sustainable Development of Elderly Care Institutions and Spatial Environmental Factors: A Study Based on the Influence of Supermarkets, Medical Accessibility, and Parks in Urban Areas - Jiang H; Guo Z; Zhang Y; Zhang H (Dove Medical Press, 2023)
Hua Jiang,1 Zhiyang Guo,1 Yuqian Zhang,1 Hangkong Zhang2 1School of Labor Economics, Capital University of Economics and Business (CUEB), Beijing, People's Republic of China; 2Institute of Gerontology, Renmin University of China (RUC), Beijing, People's Republic of ChinaCorrespondence: Yuqian Zhang, Capital University of Economics and Business, Flower-Town, Fengtai District, Beijing, 100070, People's Republic of China, Tel +86-13240943824, Email yqzhangdd@Outlook.comPurpose: To study the relationship between three variables, namely, the number of supermarkets around, the average distance to medical institutions designated to be covered by basic medical insurance, and the presence of parks around, and the sustainable development of elderly care institutions.Patients and Methods: This paper is based on the census database of elderly care institutions in Beijing. We ran a self-developed Python program to mine the database after adding three variables, namely, the number of supermarkets around, the average distance to medical institutions designated to be covered by basic medical insurance (hereinafter referred to as "designated medical institutions"), and the presence of parks around, and then used the least squares method in regression analysis.Results: The number of years of depreciation for fixed assets had some degree of influence on the occupancy rate of an elderly care institution under sustained operation. The occupancy rate of above 80% was efficient for an elderly care institution. There was a progressive relationship between the external spatial factors and the internal resources of an elderly care institution in terms of influencing the occupancy rate of the institution. Optimizing the spatial distribution of elderly care institutions should first optimize the choice of location.Conclusion: The occupancy rate of an elderly care institution was closely related to the convenience of living conditions and that site selection was crucial for such a facility. We arrived at two recommendations for the future development of elderly care institutions, 1. Reducing the number of the institutions in areas with unfavorable geographic positions and serving senior care needs within an appropriate close distance, so as to better optimize the spatial distribution of senior care facilities, improve the efficiency of resource allocation. 2. Strike a balance between the economic benefits of operating entities and the social benefits associated with older people.Keywords: elderly care institutions, bed occupancy rate, spacial environment, progressive relationship